Analisis Neraca Perdagangan Terhadap Cadangan Devisa Di Indonesia (1975-2016) - Khalwat Asyaria; Risanda A. Budiantoro; Sri Herianingrum (Jurnal Ekonomi, 2019)
Foreign exchange reserves are assets of a central bank that are stored in foreign currencies such as dollars, euros, yen and are used for international trade and funding the country's economy. The size of the country's foreign exchange reserves depends on the strength of its exports and imports both oil and gas and non-oil and gas. The purpose of this study is to analyze the allocation of oil and gas and non-oil gas trade to the volatility of foreign exchange reserves in Indonesia, 1975-2016. This study used secondary data from the Badan Pusat Statistik and World Bank reports using quantitative analysis (multiple linear regression test). The results of the study show that non-oil exports and imports have a significant negative effect on the volatility of foreign exchange reserves. While for oil and gas exports and imports it has a negative and insignificant effect.